Banking in Europe : the single market - Dixon, Rob. (Routledge, 1993)
Introduction to banking in the European community. The European Community and the single market programme. The current position and the Commission's approach. The legislative measures. Banking strategies for 1992. Preparations and attitudes of the major UK banks. Economic aspects of a single market in financial services.